2013
DOI: 10.1111/iwj.12186
|View full text |Cite
|
Sign up to set email alerts
|

Low‐grade elastic compression regimen for venous leg ulcers – an effective compromise for patients requiring daily dressing changes

Abstract: Venous leg ulcers affect millions of patients worldwide and are a tremendous financial burden on our healthcare system. The hallmark of venous disease of the lower extremities is venous hypertension, and compression is the current mainstay of treatment. However, many patients are noncompliant, in part because of the complexity of the dressings and the difficulties with application and removal. The aim of our study was to determine an effective compression dressing regimen for patients with venous leg ulcers wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Our recent pilot trial showed that tubular elastic bandages are a good compromise in stasis ulcers requiring frequent dressing changes. 25 Pressure-relieving devices and surfaces. Pressurerelieving devices and surfaces (including beds, mattresses, and cushions) are meant to redistribute pressure and are used as treatments for pressure ulcers.…”
Section: General Therapeutic Modalitiesmentioning
confidence: 99%
“…Our recent pilot trial showed that tubular elastic bandages are a good compromise in stasis ulcers requiring frequent dressing changes. 25 Pressure-relieving devices and surfaces. Pressurerelieving devices and surfaces (including beds, mattresses, and cushions) are meant to redistribute pressure and are used as treatments for pressure ulcers.…”
Section: General Therapeutic Modalitiesmentioning
confidence: 99%
“…The final sample had 22 articles, as shown in Chart 2, encompassing 15,931 individuals aged 35 years or over. Eleven studies (50%) included participants from South America (18)(19)(25)(26)(27)(28)(29)(30)(31)(32)(33) , four (18%) from North America (34)(35)(36)(37) , four (18%) from Europe (38)(39)(40)(41) , one (4%) from Australasia (42) , one from Asia (43) and another (4%) from Oceania (44) . The longest follow-up time was 13 years (35) , and the lowest time was 28 days (33) .…”
Section: Resultsmentioning
confidence: 99%
“…In all articles there was always an author from nursing departments or institutions. There were several study designs divided as follows; one of each (5%): longitudinal (18) , comparative analysis (36) , qualitative analysis (32) , case-control (27) , descriptive (33) and observational (35) ; two of each (9%): cross-sectional (26,44) and retrospective (28,33) ; three of each (14%): cohort (28,34,40) and case reports (19,29,31) ; and eight (36%) clinical trials (25,30,(37)(38)(39)(41)(42)(43) , among which four (18%) were controlled trials comparing two or more types of compression therapies, and taking into consideration the rate of reduction or healing of the injury as an evaluation parameter, as described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations